Painters painting [videorecording (DVD)] - De Antonio, Emile; De Antonio, Emile; Leider, Philip, 1929-; De Kooning, Willem, 1904-1997; Newman, Barnett, 1905-1970; Stella, Frank; Johns, Jasper, 1930-; Rauschenberg, Robert, 1925-2008; Pollock, Jackson, 1912-1956; Pavia, Philip, 1915-2005; Warhol, Andy, 1928-1987; Noland, Kenneth, 1924-2010; et al. (Arthouse Films : Distributed in the U.S. by New Video, 2010)
Emile de Antonio was a close friend to many New York painters who later went on to become famous. He filmed and interviewed them informally in their studios. Artists included are Willem de Kooning, Andy Warhol, Robert Motherwell, Barnett Newman, Jules Olitski, Frank Stella, Robert Rauschenberg, Jasper Johns, Larry Poons, Thomas Hess, Hilton Kramer, Jackson Pollock, Robert Scull, Leo Castelli, William Rubin, Henry Geldzahler, Helen Frankenthaler, Kenneth Noland, Larry Poons, Phillip Pavia, and Hans Hoffman.